Pengembangan E-Book Berbasis Model TaRL (Teaching at The Rigth Level) sebagai Bahan Ajar dalam Pembelajaran Literasi Dasar Membaca di Sekolah Dasar - Ahyar, Ahyar; Fitriati, Ita; Nurgufriani, Anita; Syarifudin, Syarifudin (Universitas Negeri Malang, 2023)
The aim of this research is to determine the feasibility and effectiveness of E-Books based on the TaRL model as teaching materials in learning basic reading literacy at elementary school level. The Teaching at The Right Level (TaRL) model is a model used to improve a person's reading ability according to their reading ability level. TaRL has been empirically proven to be able to improve students' reading abilities. This research was designed using the Research & Development method, Design Based Research model. Data was obtained using questionnaire instruments, observations and interviews. Questionnaires are needed to validate media and materials followed by interviews. The results of this research are in the form of an E-Book product which contains basic reading literacy learning packages for each reading ability level group. The results of product validation tests by media experts show that this E-Book is valid with several notes. Meanwhile, the results of validation tests by material experts show that this E-Book is valid, provided that its contextual value is increased by local stories typical of the local area. This e-book is also effective based on limited response from those who use it on a small scale. Thus, E-Books with the TaRL model are declared very suitable and effective for use in learningAbstrakTujuan penelitian ini yakni untuk mengetahui kelayakan dan efektivitas E-Book berbasis model TaRL sebagai bahan ajar dalam pembelajaran literasi dasar membaca pada jenjang SD. Model Teaching at The Right Level (TaRL) merupakan model yang digunakan untuk meningkatkan kemampuan membaca seseorang sesuai tingkat kemampuan baca. TaRL terbukti secara empiris mampu meningkatkan kemampuan baca pebelajar. Penelitian ini didesain menggunakan metode Research & Development model Design Based Research. Data diperoleh dengan menggunakan instrumen kuisioner, observasi dan wawancara. Kuisioner diperlukan untuk validasi media maupun materi yang dilanjutkan dengan wawancara. Hasil penelitian ini berupa produk E-Book yang memuat paket pembelajaran literasi dasar membaca untuk masing-masing kelompok tingkat kemampuan membaca. Hasil uji validasi produk oleh ahli media menunjukkan bahwa E-Book ini valid dengan beberapa catatan. Sementara hasil uji validasi oleh ahli materi diketahui bahwa E-Book ini valid dengan catatan supaya nilai kontekstualnya bertambah dengan cerita lokal khas daerah setempat. E-Book ini juga efektif berdasarkan tanggapan terbatas dari yang memanfaatkan dalam skala kecil. Dengan demikian E-Book dengan model TaRL dinyatakan sangat layak dan efektif untuk digunakan dalam pembelajaran.